PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN (STUDI KASUS PADA UMKM ARTSHOP DHARMASETYA DESA SUKARARA KABUPATEN LOMBOK TENGAH - I made Murjana; Erviva Fariantin; Ulfiyani Asdiansyuri (Fakultas Ekonomi Universitas Islam Al-Azhar, 2021)
This Research is The Effect of Corporate Social Responsibility (Csr) on Financial Performance (Case Study at Umkm Artshop Dharmasetya, Sukarara Village, Central Lombok Regency, with the aim of looking for the partial and simultaneous influence of environmental cost variables (x1) and employee costs (x2) on performance. financial (Y). This type of research is associative. The first result of this study is the influence of environmental cost variables on financial performance with a t value of 10,004 with a t table of 1.688 which has a partially significant effect and the influence of employee costs on financial performance with t value of 2.825 with t table of 1.688 has a significant effect partially.The second result shows that the variable environmental costs and employee costs have a simultaneous influence, namely the calculated f value is greater than the f table 136.264> 2.87 states there is a significant influence s simultaneously on financial performance.